Robust porous aerogel frameworks with high oil absorption derived from hierarchical nanocellulose/lipid nanoparticle composites - Chen, Dechu; Lee, Yee Ying; Tan, Chin Ping; Wang, Yong; Qiu, Chaoying (Elsevier, 2025)
Nanocellulose aerogels featuring lightweight and hierarchical pore structures hold significant promise in food and pharma applications. However, maintaining stable frameworks while achieving high oil absorption remains challenging due to the inherent polar nature of nanocellulose. Herein, we present a foam−template method utilizing biodegradable solid lipid nanoparticles (SLN) and bacterial cellulose (BC)/acetylated cellulose nanofibers (AA−CNF) based on their assembly strategy. This method fully leverages the structural of nanocellulose as a framework material and the SLN as wettability tailoring component. The hydrogen bonding interaction and crystal−oriented deposition facilitates the construction of robust porous structures with enhanced oil absorption. The aerogel exhibits honeycomb architectures and exceptional compression capabilities. Epicuticular lipid microvilli impart multi−level surface roughness and significant hydrophobicity (138–140°), concurrently enhancing mechanical strength. The aerogel exhibits high oil absorption capacities (100–140 g/g) and the as prepared oleogels display a high elastic modulus (∼1.5 × 106 Pa). The templating approach enables structuring of liquid oils into semi−solid oleogels, representing a healthier alternative to saturated fats. The aerogels are also ideal thermal insulation materials with higher insulation ability in presence of SLN. Capitalizing on their hierarchical structure, the multifunctional hybrid aerogels prepared by the green and scalable foam−templated approach employing nanocellulose and lipid particles prove effective as both oleogel skeletons and thermal insulators.